Sigmoid volvulus in pregnancy: a rare case - Barkase, Akanksha A.; Salunke, Chetana U.; Gawandi, Prabhakar S.; Sathe, Vijaysinha P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Sigmoid volvulus in pregnancy is an extremely uncommon condition, with only 84 cases to have been reported in the English literature. Sigmoid volvulus is the most common cause of bowel obstruction complicating pregnancy, accounting for up to 44 per cent of cases. Overall bowel obstruction in pregnancy varies from 1 in 1500 to 1 in 66,431 deliveries. Intestinal obstruction in pregnancy can be caused by many factors including congenital or postoperative adhesions, volvulus, intussusceptions, hernia and appendicitis, history of intestinal tuberculosis. Patient presented with acute onset abdominal distension associated with multiple episodes of vomiting. When history and clinical examination was suggestive of acute abdomen, diagnosis was confirmed with imaging modalities like abdominal ultrasound, CT (Computerized tomography) scan. Sigmoid volvulus is a surgical emergency and is to be treated promptly. Here we presented a case report on sigmoid volvulus in third trimester pregnancy which was managed by emergency exploration.